The Effect of Nearest Neighbor [Pb O] Divacancy Pairs on the Ferroelectric-Relaxor Transition in Nano-Ordered Pb(Sc1/2 Nb1/2)O3 - Burton, B. P. (2009)
Molecular dynamics simulations were performed on a first-principles-based effective Hamiltonians for chemically short-range ordered Pb(Sc1/2Nb1/2) O3 with nearest neighbor [Pb O] divacancy pairs. The divacancy-concentration (X[Pb-O]) vs. temperature phase diagram was calculated, and it is topologically equivalent to the hydrostatic pressure (P) vs. temperature diagram: a ferroelectric ground-state phase at low X[Pb-O] (P); that transforms to a relaxor paraelectric phase at moderate X[Pb-O] (P); followed by a crossover to a normal paraelectric phase at high X[Pb-O](P).